(untitled) (Research, Society and Development, 2020)
Studies about the structural analysis and spatial arrangement of Cactaceae are important to understand the population dynamics in natural ecosystems, as well as they can assist future programs of use and conservation. Therefore, the objective of this study was to evaluate the spatial distribution of Tacinga inamoena in a preserved caatinga area in the Cariri Paraibano microregion. 100 plots with dimensions of 10 m x 10 m were plotted in each area. Within the plots, all individuals were labeled and the total height and circumference were measured at the base of the stem with the aid of a tape measure. The spatial structure of the populations was obtained by collecting the geographical coordinate of each individual in each area and expressed through maps of spatial distribution. 34 specimens were sampled in the sampling area, presenting a basal area (AB) of 0.02 m2, absolute density (DA) of 34 ind.ha-1 and absolute frequency (FA) of 6%, being arranged in aggregates (IGA=5,49). The individuals of Tacinga inamoena have a habit of aggregate growth and population structure in the process of being established in preserved caatinga.